Evaluating the March 27, 2013 M 6.2 Earthquake Hypocenter Using Momentary High-Conductivity Materials - Chieh-Hung Chen; Cheng-Horng Lin; Han-Lun Hsu; Chung-Ho Wang; Lou-Chuang Lee; Peng Han; Strong Wen; and Chow-Son Chen (Terrestrial, Atmospheric and Oceanic Sciences, 2015)

(untitled)
Seismo-magnetic anomalies induced from the momentary existence of current and/or high-conductivity materials have been widely reported. The Parkinson vectors derived from 3-component geomagnetic data at 3 stations were obtained via the magnetic transfer function and discussed with respect to the location (23.90°E,(23.90°E, 121.07°N)121.07°N) and the depth (15.1 km) of the M 6.2 earthquake on March 27, 2013 in Taiwan. Azimuth distribution constructed from the entire Parkinson vectors during the observation period is utilized to estimate the persistent background (i.e., the coast effect and underlying inhomogeneous tectonic structures) at each station. The normalized background distribution is subtracted from the normalized monitoring distributions computed using the azimuths of the Parkinson vectors within a 15-day moving window to determine the anomalous azimuths of high-conductivity materials. The depth ranges of high-conductivity materials are evaluated when the magnetic transfer function is subjected to the skin effect. The analytical results show that high-conductivity materials appeared in areas (121.25°E,(121.25°E, 23.70°N)23.70°N) and about 10 - 25 km in depth. The location of the high-conductivity materials is about 32 km away from the epicenter reported by the Central Weather Bureau and well covers the hypocenter depth. The agreement sheds lights on forecasting locations and hypocenter depths of forthcoming earthquakes via momentary existence of earthquake-related high-conductivity materials.